Preparation and structural characterization of template assisted electrodeposited copper nanowires - Irshad, M.I. (2014)
Metallic nanowires have potential applications in miniaturized metallic interconnects, sensors and heat sink materials. In this work, highly aligned amorphous copper nanowires have been prepared by electrodeposition technique using anodized aluminium oxide (AAO) templates at room temperature. FESEM analysis shows that the as-deposited nanowires are parallel to one another and have high aspect ratio with a reasonably high pore-filing factor. The electrolyte used, consisted of a bath solution containing CuCl2.6H2O buffered with H3BO3 and acidified by dilute H2SO4. To fabricate the working electrode, a thin film of aluminum (Ì 152 nm thick) was coated on back side of AAO template by e-beam evaporation system to create electrical contact. During the electrodeposition process, the copper ions were guided to move through nano-pores where they were reduced to form one dimensional structure of pure copper nanowires. The lengths of deposited nanowires could be controlled by deposition time, applied voltage, composition of precursors. The electrodeposited nanowires have diameter varying from 15-200 nm. TEM results show that the as-deposited nanowires were dominantly amorphous with small portion of crystalline structure. Â© 2014 The Authors.